Implementasi Manajemen Sarana dan Prasarana dalam Peningkatkan Kinerja Guru - Farah Diva; Slamet Sholeh; Ilham Fahmi (CENDEKIA, 2022)
This research was conducted at Mts Al- Ahliyah. Facilities and infrastructure are one of the supporting factors for the success of teaching and learning activities, namely helping students to easily understand subjects, facilities and infrastructure can also help educators to convey the material to be discussed or delivered. With good management of facilities and infrastructure, teacher performance will increase, because one of the factors that affect teacher performance is the availability of adequate facilities and infrastructure. Because of this, this paper will discuss the management of facilities and infrastructure and improving teacher performance. The purpose of this study is to find out how important infrastructure is to improving teacher performance. The research uses descriptive methods and data collection techniques are literature studies and interviews. The results showed that the management of facilities and infrastructure can affect the performance of teachers in schools. The more and better the facilities and infrastructure in schools, the better the performance of teachers in schools.